Development of an Electronic Module (E-Module) Based on The Independent Learning Curriculum in Economics Subject for Class X SMA - Sholihah, Shofi Nimatus; Susanti; Wulandari, Siti Sri (Jurnal pendidikan ilmu sosial (Online), 2023)
The aim of this research is to analyze the feasibility of e-module based on the Independent Learning Curriculum in Economics subjects for class X SMA. This development research applies the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation and evaluation. The research was conducted at SMA Negeri 1 Sidayu in class X-5 with test subjects of 36 students. The research instruments used in this research were validation sheets and student response questionnaires. While the data analysis technique in this study is quantitative and qualitative data analysis obtained from the validation of experts, namely material expert, language expert and graphic expert, as well as student response questionnaires with assessment score criteria using a likert scale which is then analyzed descriptively. The research results based on expert validation, stated that the material expert validation results were 90.95% in the very feasible category, the language expert validation results were 80% in the feasible category, and the graphics expert validation results were 96% in the very feasible category. Meanwhile, students' responses to the e-module received an average of 83,4% in the very feasible category.